Előjáték Kopácsi Judit A hősök nem sírnak c. könyve alapján készült Számonkérés filmhez
Revolution of 1956, discussion of the film, archive pictures, newspaper clippings, radio speech, interviews with revolutionaries, István Zolcsák, school board of secondary grammar school Károly Kós, Judit Kopácsi's diary from 1956 and after, selecting children for the film, parents, stigmatisation, school principal not endrosing shooting, political committments, Tom Lantos Lajos Paulus